Electronic Dance Music as a Creative Economy Product in Indonesia: A Social and Economic Analysis - Ardiyanto, Yoga (Pascasarjana Institut Seni Indonesia Padang Panjang, 2024)
This research examines the development of Electronic Dance Music (EDM) as a commodity in Indonesia and analyzes its accompanying challenges and moral considerations. EDM has rapidly evolved into a high-value commodity within Indonesia's entertainment and creative industries. Through literature study, this research identifies several key challenges in the development of EDM as a commodity, including illegal music distribution, copyright issues, the balance between commercial value and artistic integrity, and the potential for over-commercialization. The findings indicate that optimizing EDM as a commodity requires a balanced approach between commercial interests and cultural preservation. Government support, collaboration between artists, strengthening of music infrastructure, and increased awareness and music education are necessary to ensure sustainable development of the EDM industry while maintaining Indonesia's cultural heritage. This research contributes to understanding the dynamics of the EDM industry in Indonesia and provides recommendations for its sustainable development..